Ethics in applied linguistics research language researcher narratives - DeCosta, Peter (Second Language Acquisition Research Series, 2016)
Explores how ethical issues are negotiated in different areas of language research, illustrating for graduate students in applied linguistics the ethical dilemmas they might encounter in the research methodology classroom and how they might be addressed. This volume serves to demystify the complex ethical decision-making process by its accounts of renowned researchers' ethical practices as they transpired on the ground and how they negotiated externally imposed research codes